The Impact of Implementing the Seven Good Habits Movement for Great Indonesian Children on Character Building in Students - A. Istiawati; Beni Habibi (Universitas Negeri Malang, 2025)
Abstract: Character education has become a national priority due to increasing social challenges and digital distractions that affect students’ discipline and sense of responsibility. Efforts to foster character have essentially been implemented through various initiatives such as morning routines, religious activities, mentoring, and counseling. However, the effectiveness of these programs has not yet yielded consistent and uniform results across all schools. Additionally, the “Seven Habits of Great Indonesian Children” program has been widely implemented; however, the findings obtained have been analyzed separately and have not yet been explained in an integrated manner. This study aims to identify and compare implementation strategies for the “Seven Habits of Great Indonesian Children” program, analyze the program’s impact, and evaluate the influencing factors. This study employs a Systematic Literature Review using an integrative review approach to analyze five articles from 2025 related to implementation strategies, character impacts, as well as supporting and inhibiting factors of the “Seven Habits of Great Indonesian Children” program. An integrative review was chosen because it can systematically and structurally synthesize various empirical research findings from different contexts and designs. Through thematic synthesis, it was found that the implementation of the seven habits is carried out through various approaches such as morning routines, pesantren culture, reflective journaling, and supercamp activities. This program consistently improves students’ discipline, responsibility, independence, and self-awareness. Success is greatly influenced by parental involvement, teachers’ role modeling, and school culture, while the main obstacles include inconsistency at home, excessive use of electronic devices, and peer influence. Further research could expand the implementation of the Seven Habits of Great Indonesian Children in other educational contexts. Strong collaboration between schools and parents can also be strengthened to maximize outcomes. Schools should also foster exemplary culture and character to provide direct learning experiences for students. Keywords: Seven habits of great Indonesian children, character education, discipline, habit formation, integrative review, systematic literature review